New insights into light spectral quality inhibits the plasticity elongation of maize mesocotyl and coleoptile during seed germination - Zhao, Xiaoqiang; Niu, Yining; Hossain, Zakir; Zhao, Bingyu; Bai, Xiaodong; Mao, Taotao (Frontiers in Plant Science, 2023)
The plastic elongation of mesocotyl (MES) and coleoptile (COL), which can be repressed by light exposure, plays a vital role in maize seedling emergence and establishment under adverse environmental conditions. Understanding the molecular mechanisms of light-mediated repression of MES and COL elongation in maize will allow us to develop new strategies for genetic improvement of these two crucial traits in maize. A maize variety, Zheng58, was used to monitor the transcriptome and physiological changes in MES and COL in response to darkness, as well as red, blue, and white light. The elongation of MES and COL was significantly inhibited by light spectral quality in this order: blue light > red light > white light. Physiological analyses revealed that light-mediated inhibition of maize MES and COL elongation was closely related to the dynamics of phytohormones accumulation and lignin deposition in these tissues. In response to light exposure, the levels of indole-3-acetic acid, trans-zeatin, gibberellin 3, and abscisic acid levels significantly decreased in MES and COL; by contrast, the levels of jasmonic acid, salicylic acid, lignin, phenylalanine ammonia-lyase, and peroxidase enzyme activity significantly increased. Transcriptome analysis revealed multiple differentially expressed genes (DEGs) involved in circadian rhythm, phytohormone biosynthesis and signal transduction, cytoskeleton and cell wall organization, lignin biosynthesis, and starch and sucrose metabolism. These DEGs exhibited synergistic and antagonistic interactions, forming a complex network that regulated the light-mediated inhibition of MES and COL elongation. Additionally, gene co-expression network analysis revealed that 49 hub genes in one and 19 hub genes in two modules were significantly associated with the elongation plasticity of COL and MES, respectively. These findings enhance our knowledge of the light-regulated elongation mechanisms of MES and COL, and provide a theoretical foundation for developing elite maize varieties with improved abiotic stress resistance.